Seismic Constraints on the Trompsburg Layered Igneous Intrusion Complex in South Africa Using Two Deep Reflection Seismic Profiles - Westgate, Michael; Manzi, Musa S. D.; James, Ian; Andreoli, Marco A. G.; Durrheim, Raymond J. (Frontiers in Earth Science, 2022)
Two yet-unpublished seismic profiles were conducted end-to-end in the early 1990s, with a southwest-to-northeast trend through the centre of the ~2400 km2 Trompsberg potential field anomaly in South Africa, attributed to a 1915±6 Ma buried, and under-examined, layered intrusion complex. The combined length of the two profiles is 108 km. Both profiles have been reprocessed and interpreted to further constrain the subsurface expanse of the Trompsberg Complex along the seismic traverse. Processing and interpretation of the seismic profiles were aided by a handful of studies found in the literature: stratigraphy and physical property measurements of borehole cores that were drilled into the complex in the 1940s; pre-Karoo lithological maps that were constructed based on boreholes in and around the investigation area; and potential field maps of the intrusion area near the town of Trompsburg. Most of the seismic reflection energy is concentrated within the top 1 km in both profiles, where localised reflectors with strong amplitudes are observed, due likely to the dolerite sills that permeate the Karoo cover. These sills obstruct seismic illumination of underlying structures due to their high acoustic impedance contrast with the surrounding softrock sediments, rendering underlying reflections challenging to identify and enhance. The base of the Karoo is confidently identified to be at an average depth of 1.5 km and several reflection packages have been identified thereunder. These are linked to Proterozoic supracrustals associated with the Witwatersrand, Ventersdorp, and Transvaal supergroups, as well as the Trompsburg Complex that intruded into them. The geometry of the Trompsburg Complex along the seismic traverse has been constrained with a moderate degree of confidence. It comprises a series of 30° northeasterly dipping reflectors near its southwestern boundary, flat reflectors near its centre at the town of Trompsburg, and 45° southwesterly dipping reflectors near its northeastern boundary. The lateral sub-Karoo extent of the complex is 60 km and its total thickness is difficult to constrain due to lack of deep reflections, but is likely between 6.6 km and 7.5 km. The complex subcrops against the Karoo cover except near the southwestern region, where it is overlaid by Waterberg Group sediments.